Selection of an optimum global gravitational model for geological mapping of Afikpo and Anambra Basins in Nigeria - Apeh, Ojima Isaac; Tenzer, Robert (Geodesy and Cartography, 2022)
Combined Global Gravitational Models (GGMs) are being used in numerous geoscience applications, most notably for gravimetric geoid modeling (in geodesy) and for geological mapping and geophysical explorations (in the Earth’s sciences). The aim of this study is to evaluate the suitability of different combined GGMs that could be used for the geological mapping of middle belt region and Southeastern Nigeria. For this purpose, we digitized geological maps of Afikpo and Anambra Basins to evaluate geological signatures implied by gravity field quantities (Bouguer gravity anomalies and vertical gravity gradient) derived from the EGM2008, EIGEN-6C4, GECO, SGG-UGM-1 and XGM2019e_2159 gravitational models. We also stochastically evaluated the performance of these GGMs by computing their Root-Mean-Square (RMS) fit with ground-based gravity measurements. The results show that the EIGEN-6C4 and XGM2019e_2159 models have the best RMS fit with the ground-based gravity data. A spatial pattern in Bouguer gravity maps (compiled using these two models) generally closely agrees with a geological configuration of the basins, while also exhibiting some more detailed geological features. Interestingly, however, despite the XGM2019e has the best fit and better mimics major geological features, the gravity image from this model does not exhibit a sediment signature in a portion of the Afikpo basin. A possible reason is that the topographic information used to recover a higher-frequency gravity spectrum of this model might suppress a gravitational signature of subsurface density structures. A comprehensive interpretation of geological features thus requires a careful analysis of existing GGMs, terrestrial gravity data as well as all other reliable geological and geophysical information.